2011
DOI: 10.2174/156720511794604552
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cognitive Decline and Rates of Conversion to Dementia in Patients with Degenerative and Vascular forms of MCI

Abstract: According to recent criteria, Mild Cognitive Impairment (MCI) represents a clinical condition with multiple cognitive presentations (amnesic and non amnesic) that can be supported by different types of brain lesions (mainly vascular and atrophic). In order to asses if the cognitive presentation and the rate of progression differ according to the type of brain pathology, two populations of MCI patients, characterized by hippocampal atrophy (n: 39) and vascular subcortical pathology (n: 36) respectively, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 0 publications
2
35
0
2
Order By: Relevance
“…Thus, heterogeneous pathological processes may exist in MCI patients, who then experience different cognitive dysfunction patterns. Different cognitive profiles are also associated with different prognoses, with episodic memory impairment regarded as a predictor of development of AD [35,39,40], whilst working memory impairment is more strongly associated with the onset of other types of dementia, such as vascular dementia and Lewy body dementia [41,42,43,44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, heterogeneous pathological processes may exist in MCI patients, who then experience different cognitive dysfunction patterns. Different cognitive profiles are also associated with different prognoses, with episodic memory impairment regarded as a predictor of development of AD [35,39,40], whilst working memory impairment is more strongly associated with the onset of other types of dementia, such as vascular dementia and Lewy body dementia [41,42,43,44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…Mild Cognitive impairment (MCI), or the presence of cognitive impairment in the absence of significant functional impairment, is arguably the most well-characterized risk factor for AD (Marra et al 2011). Across studies, MCI is associated with both increases and decreases in CBF, with increases in the MTL, anterior cingulate, insula, putamen, the left hippocampus, right amygdala, ventral striatum and the basal ganglia (Dai et al 2009; Alexopoulos et al 2012; Wolk and Detre 2012; Wierenga et al 2014), and decreases that reflect a lateral temporo-parietal-frontal pattern, extending to the MTL, posterior cingulate, and precuneus (Johnson et al 2005; Xu et al 2007; Dai et al 2009; Bangen et al 2012; Alexopoulos et al 2012; Wolk and Detre 2012; Wierenga et al 2014).…”
Section: Cbf In Cognitive Riskmentioning
confidence: 99%
“…In this respect, it should be taken into account that cognitive characteristics of MCI individuals might correlate with performance on CDT. It is very important to acknowledge at this point that MCI patients are rather heterogeneous from the etiological point of view and that amnesic MCI can be considered as that most related to development of AD [95,96]. In line with this caveat is the fact that, a recent study contrasting MCI of the amnesic, dysexecutive, or multi-domain type on CDT [97] confirmed that aMCI did not differ from a matched sample of healthy controls, whereas both dysexecutive and multi-domain MCI individuals made a significantly larger number of errors in hand and number placement.…”
Section: Drawing Disorders In Prodromic (Amci) and Clinical Forms Of Admentioning
confidence: 99%